(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2017)
In mobile ad-hoc networks (MANETs), an essential requirement for the foundation of communication among nodes is that nodes should coordinate with one another. In the presence of malicious nodes, this requirement may lead serious security concerns; for instance, such node may disturb the routing process. In this context, preventing or detecting malicious nodes launching grayhole or collaborative black hole in challenge. This project attempts to determine this issue by designing a dynamic source routing (DSR)- based routing mechanism, which is referred to as the cooperative bait detection scheme(CBDS), that coordinates the advantages of both proactive and reactive defence architectures. Our CBDS system implements a reverse tracing technique to help in achieving the stated goal. Simulation results are provided, showing that in the presence of malicious node attacks, the CBDS outperforms the DSR, 2ACK, and best-effort fault-tolerant routing (BFTR) protocols (chosen as benchmarks) in terms of packet delivery ratio and routing overhead (chosen as performance metrics).